A88 PATIENT AND PHYSICIAN PERSPECTIVE OF TELE-HEALTH IN GASTROENTEROLOGY. (4th March 2021) - Tomaszewski, M; Zhao, B; Kim, H; Enns, R A; Bressler, B; Moosavi, S
Abstract: Background: Given the social distancing measures employed to reduce the transmission of SARS-CoV-2, tele-health has rapidly expanded and is now routinely used in new patient encounters and in follow up appointments across Canada. Aims: To determine the patient and physician perspective towards tele-health in a gastroenterology outpatient setting. Methods: An anonymous voluntary online survey was distributed to patients who had previously undergone at least one tele-health visit in a tertiary care gastroenterology outpatient setting. A separate online survey was distributed to gastroenterologists practising across Canada. Results: A total of 181 patients from British Columbia (59.8% female) completed the survey. The tele-health appointment was the first visit for 21.8% of patients. Appointments occurred by phone call alone (61.4%) or by video and audio software (38.6%) and started within 5 minutes of the scheduled time in 75% of visits. Patient satisfaction with the tele-health visit was high (8.54 on a scale of 0–10; 0 completely dissatisfied, 10 extremely satisfied; IQR 8–10). Most patients did not perceive a difference in likelihood of compliance compared to a non-tele-health visit (90.6%), were not concerned about the lack of physical exam during a tele-health visit (82.4%) and did not with-hold information they would have revealed in person (88.7%). After the COVID-19 pandemic, some patients would prefer tele-heath visits (39.2%), whereas others would prefer in office visits (28.5%) and the remainder were indifferent (32.3%). Post-pandemic, most patients would prefer tele-health for follow up visits (68.4%), over tele-health for all possible visits (27.9%) or no tele-health visits (3.8%). A total of 25 Canadian gastroenterologists (28.0% female; 60% academic practice, 40% community practice) completed a separate survey. Regarding the lack of physical exam in tele-health, 44% of physicians believed this did not affect the quality of their assessment, whereas some physicians believed it had either minimally (48%) or greatly (8%) impaired the quality of their assessment. Almost all physicians (96%) perceived that patients either appreciate tele-health as much as or more than in office visits. Post-pandemic, most physicians (96%) supported a hybrid model of both tele-health and in office visits. Appointments for follow up of benign endoscopic pathology results (96%), follow up visits (92%), consultations prior to endoscopy (76%) were deemed to be most appropriate for tele-health. Follow up of malignant pathology results (24%) and consultations for new patients (32%) were thought to be less appropriate for tele-health visits. Conclusions: Patient and physician satisfaction with tele-health in a Canadian outpatient gastroenterology setting is high. Most patients and physicians wish for tele-health to remain available in the post-pandemic setting. Funding Agencies: Gastrointestinal Research Institute, Vancouver, British Columbia